Free-standing nanogold membranes as supports for the growth of calcium phosphate crystals - Rautaray, D; Sastry, M (Biotechnology Progress, 2005)
Current strategies for bone tissue regeneration focus on the development of implantable matrices that mimic biological tissues. Inorganic composites are of special interest for bone substitute applications. It is necessary to create an artificial three-dimensional scaffold-like porous material with certain geometrical structure to induce bone growth. We report here the growth of calcium phosphate crystals on free-standing carboxylic acid functionalized gold nanoparticle membranes. The gold nanoparticle membrane is synthesized by the spontaneous reduction of aqueous chloroaurate ions by a diamine molecule at a liquid-liquid interface. This membrane is robust and malleable, and most importantly, the gold nanoparticles in the membrane may be functionalized with suitable ligands. In this study, the amino acids aspartic acid and cysteine together with an aromatic bifunctional molecule, anthranilic acid, were used to modify the surface of the gold nanoparticles in the membrane. The free carboxylic acid groups on the gold nanoparticles further to functionalization with these molecules were then used to bind Ca2+ ions and reacted with phosphate ions to yield calcium phosphate. The nature of the nanogold surface modifier directed the formation of either crystalline hydroxyapatite or amorphous calcium phosphate. The nanogold membrane thus suggests potential biomedical application as biocompatible implants and grafts.